The present document can't read!
Please download to view
All materials on our website are shared by users. If you have any questions about copyright issues, please report us to resolve them. We are always happy to assist you.
...

CONTOH-CONTOH SOAL

by guglielmo-blaney

on

Report

Category:

Documents

Download: 0

Comment: 0

49

views

Comments

Description

CONTOH-CONTOH SOAL. BAB 2 OPERASI HIMPUNAN. Contoh 2.1:. Misalkan diketahui himpunan-himpunan U, A,B,C : U={a,b,c,d,e,f,g}A={a,b,c,d,e} B={a,c,e,g} C={b,e,f,g}. Tentukan : A  C 2. B  A 3. C - B 4. B ’ 5.A ’ - B - PowerPoint PPT Presentation
Download CONTOH-CONTOH SOAL

Transcript

  • CONTOH-CONTOH SOAL BAB 2 OPERASI HIMPUNAN
  • Contoh 2.1: Misalkan diketahui himpunan-himpunan U, A,B,C : U={a,b,c,d,e,f,g} A={a,b,c,d,e} B={a,c,e,g} C={b,e,f,g} Tentukan : AC 2. BA 3. C-B 4. B’ 5.A’-B B’ C 7. (A-C)’ 8. C’ A 9. (A-B’)’ 10. (A A’)’
  • Jawab : U={a,b,c,d,e,f,g} A={a,b,c,d,e} B={a,c,e,g} C={b,e,f,g} AC ={a,b,c,d,e,f,g}=U BA ={a,c,e} C-B={b,f} B’ ={b,d,f} A’-B ={f}
  • B’ C ={b,d,e,f,g} (A-C)’ = {b,e,f,g} C’ A = {a,c,d} (A-B’)’ = {b,d,f,g} (A A’)’ = U U={a,b,c,d,e,f,g} A={a,b,c,d,e} B={a,c,e,g} C={b,e,f,g}
  • Contoh 2.2: Diketahui diagram Venn : Lakukan arsir pada himpunan-himpunan berikut : V  W 2. W’ 3. W-V 4. V’ W 6.A’-W’ V W U
  • Jawab: V W U 1. V  W (arsir kotak) V
  • Jawab: V W U 2. W’ (arsir miring) W V
  • Jawab: V W U 3. W-V (arsir miring) V W
  • Jawab: V W W . 4. V’W (arsir miring) U . W . V .
  • Jawab: V W U 5. VW’ (arsir miring) W V
  • Jawab: V W U 6. V‘-W’ (arsir miring) W V
  • Contoh 2.3: Gambarkan diagram Venn untuk tiga himpunan A, B dan C yang tidak kosong () bila diketahui : AB, C B, AC =  A  B, CB, AC  A  C, A  C, BC =  A (B  C), B C, C  B,A C
  • Jawab: AB, C B, AC = 
  • Jawab: A  B, CB, AC 
  • Jawab: A  C, A  C, BC = 
  • Jawab: A (B  C), B C, C  B,A C
  • Contoh 2.4 : Buktikan persamaan-persamaan berikut : B – A’ =BA 2. A’ - B’=B - A Jawab : B – A’ ={x|xB, xA’}={x |xB,x  A}= BA 2. A’ - B’={x | xA’, xB’}={x|xA, x  B}=B-A
Fly UP